New pricing models for generic medicines to ensure long-term sustainable competition in Europe - Francois, Clement; Gawlik, Gabriela; Mestre-Ferrandiz, Jorge; Pana, Adrian; Perelman, Julian; Yfantopoulos, John; Simoens, Steven (Frontiers in Pharmacology, 2023)
BACKGROUND: Price erosion of generic medicines over time as a result of existing pricing policies in combination with increasing operational costs of these products due to high inflation, undermine long-term sustainable competition in European off-patent medicines markets. Therefore, the aim of this study is to identify new potential pricing models for retail generic medicines in Europe, examine their pros and cons, and illustrate them with examples inside or outside the pharmaceutical sector.METHODS: A targeted literature review, one-to-one interviews and a joint advisory board meeting with experts from five European countries were carried out to assess potential pricing models for generic medicines. RESULTS: We identified ten pricing models that can be applied to generic medicines. The tiered pricing model is viewed as a sustainable solution ensuring competitiveness, but requires market monitoring using a supportive IT infrastructure. De-linking the price of generic medicines from that of the off-patent originator medicine prevents the originator from forcing generic medicines' prices to unsustainable levels. Higher costs due to inflation can be compensated in the automatic indexation model. Other pricing models that have less implementation potential include the one-in-one/multipleout model, tax credits, value-based pricing, volume for savings and guaranteed margin/fee models. This is a provisional file, not the final typeset articleThe hypothecated tax and cost allocation models, which add a patient fee to generic medicines prices, are not likely to be socially acceptable.CONCLUSION: When considering a new pricing model for generic medicines, the impact on innovative medicines and the characteristics of the health care system in a given country need to be taken into account. Also, there is a need to continuously follow up the level of competition in offpatent medicines markets and to identify sustainability risks.